2021
DOI: 10.1109/access.2021.3099111
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Time-Series Framework for Daily-Based PM2.5 Forecasting

Abstract: The impact of fine particulate matter on health has captured attention worldwide. Many studies have proven that fine particulate matter harms the respiratory system and the cardiovascular system. To prevent people from being harmed, many scientific research studies on PM 2.5 prediction have been conducted in recent years. Accurate PM 2.5 forecasting can not only alert people to stay away from concentrated areas but also provide the government with environmental policies in the future. In this paper, we propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…( 2018 ) apply a similar hybridisation in which an MLP is also combined with a CNN and a spatio-temporal LSTM. A hybrid model which combines LSTM, GRU and CNN is developed by Chiang and Horng ( 2021 ) to forecast daily PM 2.5 in Taiwan.…”
Section: Classification By Used Model Of the Contributions On Air Qua...mentioning
confidence: 99%
“…( 2018 ) apply a similar hybridisation in which an MLP is also combined with a CNN and a spatio-temporal LSTM. A hybrid model which combines LSTM, GRU and CNN is developed by Chiang and Horng ( 2021 ) to forecast daily PM 2.5 in Taiwan.…”
Section: Classification By Used Model Of the Contributions On Air Qua...mentioning
confidence: 99%
“…This layer can be used for object recognition, segmentation, and classification by learning patterns from images or videos using multiple layers with different parameters and associated weights. Recent advances in deep learning have shown that CNNs can also be used for time series prediction [79,80] and nonlinear regression [81].…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…In addition, predictive models for PM 10 and PM 2.5 based on neural ensemble techniques were developed [18]. Chiang and Horng proposed a hybrid time-series prediction framework including an autoencoder, dilated CNN, and GRU to predict PM 2.5 [19].…”
Section: Reportedmentioning
confidence: 99%